The x^3 is throwing me off!
Studying Linear and Nonlinear Systems of Equations:
Solve the system by method of substitution
y = -x
y = x^3 + 3x^2 + 2x
I started by substituting -x for y -x = x^3 + 3x^2 + 2x x^3 + 3x^2 + 3x = 0
then my next step was to group (x^3 + 3x^2) + 3x = 0 distribute - x^2(x - 3) + 3x = 0
Would my next step be (x^2 + 3x)(x-3) Help!
Studying Linear and Nonlinear Systems of Equations:
Solve the system by method of substitution
y = -x
y = x^3 + 3x^2 + 2x
I started by substituting -x for y -x = x^3 + 3x^2 + 2x x^3 + 3x^2 + 3x = 0
then my next step was to group (x^3 + 3x^2) + 3x = 0 distribute - x^2(x - 3) + 3x = 0
Would my next step be (x^2 + 3x)(x-3) Help!